Cyber-proletariat and Cyber-bourgeoisie: A Foucauldian Investigation of the Cyber-workplace. - Walberg, Serge (International Journal of the Humanities, 2007)
The advent of the internet has spawned a burgeoning cyber-proletariat, with armies of online workers, dispersed globally, collaborating in the development of online products and services. In the wake of the success of the Call Centre phenomenon, global corporations were quick to avail themselves of cheap (yet highly skilled) low-level computing practitioners in developing countries, handling millions of online operations daily, yet receiving much lower wages than their western counterparts. This work investigates the cyber-workplace and its populations, the interactions between cyberworkers and non-working internet surfers, the new phenomenon of tele-commuting, and the effects on electronic democracy of the appearance of a "cyber-lumpen-proletariat". The emergence of BPO (Business Process Outsourcing) allows global corporations to outsource a huge volume of low-level computing (mostly updating of client databases for banks, insurance companies and health-care institutions) to developing countries (primarily India and the Philippines) where labour costs are considerably lower than in western countries, and where workers are often less protected (sometimes not protected) by legislation or trade unions. This in effect creates a "live-in diaspora" of cyberworkers who are working abroad but living at home. As with the industrial revolution which produced a proletariat and a lumpen-proletariat, this cyber-revolution has created a cyber-proletariat populating cyber-sweatshops and even a cyber-lumpen-proletariat, or a reserve pool of unemployed cyber-workers. This paper will use a Foucauldian perspective to investigate concepts of electronic democracy applied to cyberspace as a new global working environment.